Experiências vividas na formação em terapia ocupacional: uma análise narrativa - Fuentes, Giovana Coler (Universidade Federal de São Carlos, 2025)
This study provides a comprehensive overview of the history of Occupational Therapy education and the specific characteristics of the program at the Federal University of São Carlos (UFSCar). It highlights the practical disciplines and mandatory supervised internships, exploring the challenges and learning experiences encountered during the formative period following the COVID-19 pandemic. Adopting a qualitative approach, the research centers on describing lived experience through four categories: lived space, lived body, lived time, and lived relation. This framework is utilized to analyze the trajectory of the narrator-researcher. Data collection involved the creation of a mind map to incorporate significant experiences throughout the academic formation, followed by the transcription of audio recordings detailing these experiences, initiating a process of reflection and analysis. The initial experience recounted refers to the imposition of a period of Emergency Non-Presential Teaching (ENPE) at UFSCar, which occurred exclusively through virtual means due to the COVID-19 pandemic starting in 2020. This circumstance evoked feelings of loneliness and uncertainty, influencing the perception of elapsed time and negatively impacting the dynamic of university life. Subsequent experiences aim to exemplify the importance of attending to the singularity of individuals, upholding professional ethical conduct, and rigorously adhering to protocols. In essence, this project demonstrates that the initial formative process in Occupational Therapy is dynamic, continuously shaped by ongoing interactions between individuals and their contexts.
Lived experiences in occupational therapy training: a narrative analysis
Keywords: Terapia ocupacional; Formação profissional em saúde; Pandemia de Covid-19; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL